How Green are Green Debt Issuers? - Schmittmann, Jochen (IMF Working Papers; Working Paper ;, 2021)
Green debt markets are rapidly growing while product design and standards are evolving. Many policymakers and investors view green debt as an important component in the policy mix to achieve the transition to a low carbon economy and ensure the pricing of climate risks. Our analysis contributes to the nascent literature on the environmental impact of green debt by documenting the CO2 emission intensity of corporate green debt issuers. We find lower emission intensities for green bond issuers relative to other firms, but no difference for green loan and sustainability-linked loan borrowers. Green bond, green loan, and sustainability-linked loan borrowers lower their emission intensity over time at a faster rate than other firms.